Navigating Linguistic Diversity: Indonesian Language Variation and Communication Adaptation among First-Year University Students - Adenia Kusuma Etacho; Aulia Novika; Fahya Dika Aurelia; Muhammad Faruq Zakiuddin; Tamara Putri Kamila (Yayasan Sagita Akademia Maju, 2026)
This study aims to examine the variation in Indonesian language use and the communication adaptation of first-year students within the multicultural environment of Universitas Pembangunan Nasional